TRABAJO COLABORATIVO PARA EL DESARROLLO DE LA INTERCULTURALIDAD, EN LA UNIDAD EDUCATIVA SAN GERARDO - Unach (2019)
The investigation was done in San Gerardo high school with seventh grade ‘’A’’ students of basic education. In this educational context there are different cultures like: mestizo and indigenous. In the particular case of indigenous’ children showed insecurity and devalued of their identity, they aren´t interesting of mestizo’s friendship, they don´t wear their typical ancestral costume, they don´t speak their typical language: kichwa, teachers also don´t show that the pedagogical strategies aren´t promoted to strengthen the intercultural education and harmonious coexistence between both cultures. The general objective of this investigation was, determine the collaborative work´s influence in the development of the interculturality. The theoretical framework show that the two variables’ study, the investigation´s design was: mixed, quantitative and qualitative data were processed, the investigation type was descriptive, bibliography and field, in this investigation the inductive method was used, here I worked with a sample of 29 students, the guide creationworked as a learning strategy, active and creative resource, after its students´ application and through the test, data was obtained across of charts and graphs with their respective analysis, the results´ discussion was made through the data´s triangulation, it was conclude that children added a perspective based on recuperation and comprehension of the cultures´ mutual enrichment that there are in the reality of their environment, the collaborative work´s activities helped in the cultures´ value such as: indigenous and mestizo, It is suggested the application of collaborative work´s guide to develop the interculturality; the proposal is based on interculturality as a transversal axis of the educational process, the guide has activities to strengthen the own culture´s love and the respect for the rest that there are inside of the educational context.